Criteria of ultrasound-guided closed reduction with percutaneous pinning in unstable humeral lateral condylar fractures: a three-center retrospective cohort study - Huang, Xiuming; Liu, Chaoyu; Jia, Guoqiang; Yao, Jie; Xu, Jianbing (Frontiers in Pediatrics, 2024)
Background: Interventions using ultrasound-guided closed reduction and percutaneous pinning (UG-CRPP) of humeral lateral condylar fractures (HLCFs) have been increasingly applied; however, their effectiveness for unstable HLCFs and the criteria for ultrasound outcomes remain unclear. This study assessed the outcomes of UG-CRPP for HLCFs and evaluated the success criteria in children.Data were retrospectively collected from 106 patients with unstable HLCFs admitted to three hospitals between January 2021 and August 2022. Fifty-five cases were left-sided and 51 cases were right-sided: 74 male patients and 32 female patients were included. Perioperative data, elbow function, complications, and criteria for UG-CRPP were analyzed.The mean rate of UG-CRPP was 88%. The mean surgical time was 54.56 ± 21.07 min, and the mean fluoroscopy frequency was 9.25 ± 2.93 times. At the last follow-up, there were significant differences in elbow flexion between the affected side (135.82°± 6.92°) and the unaffected side (140.58°± 5.85°) (P = 0.01). The Mayo score of the affected side was 90.28°± 4.97°, the Baumann angle was 71.4°± 5.4°, condylar shaft angle was 39.9°± 6.4°, and the carrying angle was 8.4°± 3.6°. Seventy patients presented mild lateral spurs and 16 patients exhibited moderate spurs.Fourteen patients presented with pin infection, and one patient exhibited postoperative re-displacement. There was no premature physeal closure, varus, or valgus elbow deformity, delayed union, or non-union. Successful ultrasound-based outcome criteria for UG-CRPP were defined as follows: (i) absent or less than a cartilage thickness step on the cartilage hinge on coronal plane parallel articular surface scanning, (ii) no lateral displacement and intact distal end of the condylar and capitellum on coronal plane vertical articular surface scanning, (iii) no anteroposterior displacement and absent or less than a cartilage thickness step on sagittal plane vertical articular surface scanning, and (iv) intact posterior fracture line or less than a cortex step on posterolateral sagittal plane vertical articular surface scanning.UG-CRPP is a procedure with minimal blood loss, less invasive, cosmetic, and no radiation exposure. It yielded good outcomes in unstable HLCFs.The successful criteria make it suitable for clinical application.